Terapia respiratoria, factor determinante en el tratamiento de bronquitis en niños de 0 a 5 años que acuden al circuito de salud Enrique Ponce Luque durante el primer semestre del 2017 - Solis Cordova, Alex Andres (2017)
In the Ecuador the leading cause of death among children under the age of 0 and 5 years corresponds to respiratory infections with a 16.4%, with a slight predisposition for male, and are the cause of most frequent medical consultation for acute pathology and cough. These reasons have motivated the realization of this scientific research, with the objective of verifying the virtues and benefits of the application of perfusionists and respiratory therapy alone or in combination to complement the medical treatment of acute bronchitis in children 0 to 5 years of age. It was considered a sample of 103 patients of a total population of 143, which went to the pediatrician in the circuit of health Enrique Ponce Luque, with diagnosis of acute bronchitis. With the data collected in the questionnaire of the survey was a database in the Microsoft Excel program for statistical analysis of variables in the study. As a result we have to 69% of cases seen in the Health circuit Enrique Ponce. L., they are referred to the hospital Martin Icaza R. nebulization technique is the most applied, mothers in 39% do not know the applied medicine and, for 5 consecutive days therapy sessions are more productive because of the improvement of the respiratory tract of infants. Testing the hypothesis that the respiratory therapy is crucial in the comprehensive treatment medical of the under-fives.